Pendampingan Pencatatan Akuntansi Melalui Sinkronisasi Faktur Penjualan di CV Angkasa Leather - Kurnia Nanda Prameswari; Habi Bullah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service activity aims to improve the efficiency and accuracy of accounting records through synchronization of sales invoices at CV Angkasa Leather. The mentoring process involves students who are given the task of checking and matching sales invoice data with the NexSoft Distribution 6 (ND6) system. The main tasks of students include checking invoices that have been sent, separating invoices based on payment status (paid and not yet paid), and separating invoices according to the name of the sales person responsible. The results of the activity show that the implementation of an invoice coloring system consisting of four colors—white, yellow, red, and green—can accelerate the identification of payment status and simplify the management of administrative archives. Through this activity, it is hoped that partners can manage sales data and accounts receivable more efficiently, accurately, and in a structured manner, as well as improve the quality of the company's accounting records as a whole.